Organizational culture influence on job satisfaction in the Pakistan context - Imran, Muhammad; Ismail, Fadillah (International Journal of Academic Management Science Research (IJAMSR), 2018)
The objective of this paper is to offer a proposed relationship between organizational culture and job satisfaction in Pakistan. Organizational culture refers to the outcome of individuals or group of people in the organization that have the same attitude as well as behavior. Job satisfaction means a situation where organization employees satisfied with their jobs. Literature shows that inconsistent results between organizational culture and job satisfaction and calls further studies. Hence, this paper proposed hypotheses between organizational culture and job satisfaction. Although, this paper is conceptual in nature thus, there a need for empirical research on this relationship in the light of social exchange theory.